Different photoisomerization routes found in the structural isomers of hydroxy methylcinnamate. Issue 26 (25th April 2018) - Kinoshita, Shin-nosuke; Miyazaki, Yasunori; Sumida, Masataka; Onitsuka, Yuuki; Kohguchi, Hiroshi; Inokuchi, Yoshiya; Akai, Nobuyuki; Shiraogawa, Takafumi; Ehara, Masahiro; Yamazaki, Kaoru; Harabuchi, Yu; Maeda, Satoshi; et al.
Abstract : Upon UV excitation, meta - and ortho -hydroxy methylcinnamate ( m -, o -HMC) isomerize via a [ trans - 1 ππ* → TS → cis -S0 ] route, while para -HMC ( p -HMC) isomerizes via a [ trans - 1 ππ* → 1 nπ* → T1 ( 3 ππ*) → cis -S0 ] route. Abstract : An experimental and theoretical study has been carried out to elucidate the nonradiative decay (NRD) and trans ( E ) → cis ( Z ) isomerization from the S1 ( 1 ππ*) state of structural isomers of hydroxy methylcinnamate (HMC); ortho -, meta - and para -HMC ( o -, m - and p -HMC). A low temperature matrix-isolation Fourier Transform Infrared (FTIR) spectroscopic study revealed that all the HMCs are cis -isomerized upon UV irradiation. A variety of laser spectroscopic methods have been utilized for jet-cooled gas phase molecules to investigate the vibronic structure and lifetimes of the S1 state, and to detect the transient state appearing in the NRD process. In p -HMC, the zero-point level of the S1 state decays as quickly as 9 ps. A transient electronic state reported by Tan et al. ( Faraday Discuss. 2013, 163, 321–340) was reinvestigated by nanosecond UV-tunable deep UV pump–probe spectroscopy and was assigned to the T1 state. For m - and o -HMC, the lifetime at the zero-point energy level of S1 is 10 ns and 6 ns, respectively, but it becomes substantially shorter at an excess energy higher than 1000 cm −1 and 600 cm −1, respectively, indicating the onset of NRD. Different from p -HMC, no transient state (T1 ) was observed in m - nor o -HMC. These experimental results are interpreted with the aid of TDDFT calculations by considering the excited-state reaction pathways and the radiative/nonradiative rate constants. It is concluded that in p -HMC, the trans → cis isomerization proceeds via a [ trans -S1 → 1 nπ* → T1 → cis -S0 ] scheme. On the other hand, in o - and m -HMC, the isomerization proceeds via a [ trans -S1 → twisting along the CC double bond by 90° on S1 → cis -S0 ] scheme. The calculated barrier height along the twisting coordinate agrees well with the observed onset of the NRD channel for both o - and m -HMC.